"Yesterday You Slaughtered Animals, Today You Pity Them": Ambivalence and Resolution Among Jewish Israeli Slaughterers. (4th May 2022) - Ben-Yonatan, Anat
ABSTRACT: This study explored the ambivalence influenced by emotional and moral concerns experienced by Israeli Jewish slaughterers regarding their everyday practices. The findings were based on 35 semi-structured, in-depth interviews with Jewish workers in the kosher slaughter industry in Israel. The manifestations of ambivalence found in the interviews were divided into three categories: between action and meaning, between emotions and religious rationality, and between human–animal similarities and differences. I concluded that, while Jewish slaughterers in Israel displayed ambivalent views about nonhuman animals, they had clear resolutions for these inner conflicts based on available moral and religious justifications for animal slaughter.